Histological Study of the Restorative Effect of Roselle (Hibiscus sabdariffa Linn.) Tea on the Digestive Organs of Monosodium Glutamate-Induced Mice (Mus musculus Linn.) - Sistra, Kanigara Anupama; Wiratmini, Ngurah Intan; Sukmaningsih, A. A.S.A. (Folia Medica Indonesiana, 2023)
Highlights: • This original study examined the antioxidant compounds derived from naturally sourced Hibiscus sabdariffa calyx. • The findings demonstrated that roselle tea offers a viable and cost-effective solution for repairing histological damage to the digestive organs induced by monosodium glutamate. Abstract Monosodium glutamate (MSG) is a commonly used synthetic additive for enhancing food flavor. Excessive use of MSG can cause cytotoxic effects, which disrupt the balance of oxidative stress and free radicals in the body, particularly in the human digestive system. Roselle (Hibiscus sabdariffa) is a plant with red petals renowned for its abundance of beneficial compounds, including polyphenols, flavonoids, anthocyanins, and other antioxidants that function as free radical antidotes. This study aimed to investigate the effect of administering roselle tea and determine the optimal dose for restoring the digestive organs of MSG-induced mice (Mus musculus). The research employed a completely randomized design with a random sampling method. A total of 25 mice were divided into five groups: a negative control group (K-) that received 0.3 mL of distilled water, a positive control group (K+) given 4 mg/g bw of MSG, and three treatment groups (P1, P2, and P3) administered with 4 mg/g bw of MSG along with varying doses of roselle tea (2.6 mg/g bw, 3.9 mg/g bw, and 5.2 mg/g bw, respectively). The treatment was orally administered via gavage for 30 days. The stomach, duodenum, and liver underwent histopathological examination using the paraffin method and hematoxylin-eosin staining. The observed parameters in the stomach and duodenum included necrosis, inflammatory cell infiltration, villous erosion, and epithelial desquamation. Meanwhile, the parameters examined in the hepatic organs were necrosis, inflammatory cell infiltration, and cell degeneration. The Kolmogorov-Smirnov normality test and one-way analysis of variance (ANOVA) were employed to assess the normal distribution and homogeneity of the data. If the data exhibited a normal distribution, Duncan's post-hoc test was conducted. The results revealed significant differences among the groups (p<0.05). In conclusion, the administration of roselle tea effectively recovered the histological damage in the stomach, duodenum, and liver of MSG-induced mice.